Application of Bibliotherapy in Gestalt Therapy: Fiction Books as a Stimulant of Personality Transformation - Girčienė, Jurgita; Žukauskienė, Daiva (Knygotyra, 2022)
The theory of the Gestalt therapy which is based on the humanist attitude towards the personality is applied in the social work, education, etc. It is considered to serve as a foundation of interactive bibliotherapy. However, as the professional discourse of the experts of Gestalt has demonstrated, and as it has been proven by the lack of research of the application of bibliotherapy in Gestalt therapy, bibliotherapy is still being underused as an option in Gestalt treatment. Generally, even though the interdisciplinary field of bibliotherapy has been extensively explored, there is an incentive to share the scarce (in terms of quantity) models of the applied nature which would define how bibliotherapy could be systematically involved into various consultation practices with the objective to enhance their efficiency.The article presents one of the possible models of practical application of interactive bibliotherapy in the Gestalt practice which is based on the triple dialogue (in interaction with the therapist) and written reflection of brief fictional texts. The model is based on the grounds of aligning the paradigms of Gestalt therapy and bibliotherapy. Cases of 60 clients who were being applied bibliotherapy throughout the 7 years of operation of one practice were explored with the emphasis on the qualitative aspect. The results of the research proved the appropriateness of bibliotherapy as a secondary means to be applied in Gestalt therapy. It has been established that, under the appropriate field conditions, the properly selected fictional text as the mediator through the dialogue-based reflection with the therapist may help the client to perceive his/her unsatisfied needs and to alter in the desired direction within a shorter timeframe, i.e., it enables personality transformation. In such cases, works of fiction serve the function of the stimulants of the authentic intrapersonal communication (i.e., one’s inner experiences and their inner reflection) and the amplifying or reinforcing function of the stimulants of interpersonal communication. This corroborates the data of neurological research indicating that fiction intensively stimulates and even (trans)forms the intellectual and emotional self- and world perception of a reading individual.The presented model of the application of bibliotherapy may be beneficial not only for the practitioners of Gestalt, but also for librarians, social workers and education specialists as well as the practitioners of therapies of other types, while especially considering the lack of systematic descriptions of the application of bibliotherapy as an additional and enhancing means, which has been highlighted in the relevant literature.
Keywords: (interactive) bibliotherapy; Gestalt (psycho)therapy; model of bibliotherapy application; (deep) reading; fiction books as stimulants of authentic intrapersonal and interpersonal communication